(untitled) (International Conference on Computing, Artificial Intelligence and Information Systems, 2026)
This article analyzes the formation and developmental stages of miniature art during the Timurid period, as well as the role of digital technologies in integrating it into the modern educational process. The study examines the development of book art, calligraphy, ornamentation, and miniature schools during the Timurid era, with particular attention to the rise of the Herat school and the artistic-aesthetic significance of Kamal al-Din Behzad’s work. In addition, the article highlights the potential of digital museums, virtual galleries, multimedia textbooks, 3D/AR/VR technologies, electronic learning platforms, and interactive methods in the teaching of art history.